Inferiorizing Indigenous Communities and Intentional Colonial Poverty - Koptie, Steven W.; Wesley-Esquimaux, Cynthia (First Peoples Child & Family Review, 2010)
This paper is a reflective topical autobiography of a man seasoned by thirty years of community and crisis work. It has been written to encourage Aboriginal peoples to reflect on their lives and share their lived-experiences with others so that we can work together to break the colonial spell that has held so many hostage to their past.